Online Education Strategies Used in Imam Hossein Hospital in Tehran during the COVID-19 Outbreak - Mehrdad Haghighi; Shahin Salehi; Mehrdad Ghasemian; Mahmoud Nouraei (Kerman University of Medical Sciences, 2020)
Background: The COVID-19 pandemic has caused many changes in the educational structure of hospitals, so much so that the educational systems tend to use online education. In this regard, the Deputy of Education of Imam Hossein Hospital designed an application to expand this form of education in the hospital. Objectives:The purpose of this study was to review various software used in online education in Imam Hossein Hospital, to obtain the strengths and weaknesses. Methods: The present investigation was a scholarly approach study performed in Imam Hossein Hospital in Tehran in several stages during the COVID- 19 outbreak (beginning of March 2020). First, the necessary infrastructure was examined through meetings held in the educational deputy of the hospital. Then, a system was created by the deputy by which teachers could upload educational files in different formats. Finally, the files uploaded by the faculty members were evaluated by the observers. Results: In this study, professors uploaded 234 files in various formats to the hospital website. PowerPoint was the most frequent format in these files, of which 105 (44.8%) were uploaded. 42 (17.9%) files were sent as images. 27 (11.5%) were multimedia files in different formats. And 17 files (7.2%) were about the evaluation of  the residents, which was conducted via Google form. Other files in total 43 (18.3%) included other formats. The average score of the educational files uploaded by the faculty members was 17.79 ± 3.26. Conclusion: Since medical education is mostly based on students' clinical practice, the lack of an exclusive platform in this area is quite noticeable. The present study showed that professors at first do not necessarily choose the best platform for providing online education, but the most familiar software available. This trend, however, may change with experience. Therefore, it is better to suggest the best platform for professors from the very beginning of online education